Recovering the damaged industrialised building system beam flexural strength for re-use - Whaib, Mahdi Sabbar (2014)
Industrialized Building System (IBS) is a construction method where components are manufactured in factory or on-situ in a controlled and monitored environment, transported and assembled with minimum workforce. This system is widely used in the worlds. Upgrading of reinforced concrete structures may be required for many different reasons. The concrete may have become structurally inadequate due to deterioration of materials, poor design, or construction, lack of maintenance, upgrading of design loads or accidental events such as earthquakes. Therefor in such conditions there are two possible solutions: replacement or retrofitting. Full structure replacement might have includes some disadvantages such as high costs for material, labor and in addition to more using time. This research details the experimental work of two case of reinforced concrete IBS beams (previously has been tested to failure) retrofitted by using external steel plate placed at the bottom soffit level of the beam, and the outer steel stirrup is covering the concrete to increase its stiffness and flexural strength have been tested under two point loading at three steps of loading. The objectives of this study were to investigate the behaviour of retrofitted beams experimentally, and be cord the mechanism of re-failure of retrofitted IBS beams in laboratory environment. The result shows that the beams recover its capacity by 60% of their original capacities.